Lower pH values of weakly acidic refluxes as determinants of heartburn perception in gastroesophageal reflux disease patients with normal esophageal acid exposure. Issue 1 (12th September 2014) - de Bortoli, N.; Martinucci, I.; Savarino, E.; Franchi, R.; Bertani, L.; Russo, S.; Ceccarelli, L.; Costa, F.; Bellini, M.; Blandizzi, C.; Savarino, V.; Marchi, S.
Summary: Multichannel impedance pH monitoring has shown that weakly acidic refluxes are able to generate heartburn. However, data on the role of different pH values, ranging between 4 and 7, in the generation of them are lacking. The aim of this study was to evaluate whether different pH values of weakly acidic refluxes play a differential role in provoking reflux symptoms in endoscopy‐negative patients with physiological esophageal acid exposure time and positive symptom index and symptom association probability for weakly acidic refluxes. One hundred and forty‐three consecutive patients with gastroesophageal reflux disease, nonresponders to proton pump inhibitors (PPIs), were allowed a washout from PPIs before undergoing: upper endoscopy, esophageal manometry, and multichannel impedance pH monitoring. In patients with both symptom index and symptom association probability positive for weakly acidic reflux, each weakly acidic reflux was evaluated considering exact pH value, extension, physical characteristics, and correlation with heartburn. Forty‐five patients with normal acid exposure time and positive symptom association probability for weakly acidic reflux were identified. The number of refluxes not heartburn related was higher than those heartburn related. In all distal and proximal liquid refluxes, as well as in distal mixed refluxes, the mean pH value of reflux events associated with heartburn was significantly lower than that not associated. This condition was not confirmed for proximal mixed refluxes. Overall, a low pH of weakly acidic reflux represents a determinant factor in provoking heartburn. This observation contributes to better understand the pathophysiology of symptoms generated by weakly acidic refluxes, paving the way toward the search for different therapeutic approaches to this peculiar condition of esophageal hypersensitivity.